Pengaruh Penggunaan Video Pembelajaran Terhadap Hasil Belajar Komputer 1 Mahasiswa Pendidikan Matematika Semester II TP. 2019/2020 Universitas Pasir Pengaraian - Arcat Arcat (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2020)
The computer 1 learning outcomes of the second-semester students of the Mathematics Education study program are low because the instruments used have not used instructional videos. A solution is needed in the form of the use of instructional videos. This study wanted to see whether or not there was an effect of instructional videos on the learning outcomes of computer 1. The quasi-experimental method used in this study was that the class A was the experimental class and class B was the control class. The sampling technique used is the saturated sampling technique, where all populations are used as research samples. The average similarity test was used in analyzing quantitative data, while the qualitative data were analyzed descriptively. The average similarity test results utilizing the t-test show where the value of tcount > ttable that 2,56 > 2,015, so it can be concluded that there is an effect of the use of instructional videos on computer 1 learning outcomes second-semester students of the mathematics education study program 2019/2020.